Application of tissue pneumoperitoneum technique around lymph nodes in thoracoscopic lung cancer resection - Wang, Fangqing; Chen, Gang; Ruan, Weimin; Wang, Binkui; Zhu, Zhaowang; Hu, Weijian; Chen, Sheng; Zang, Lin (Frontiers in Oncology, 2024)
BackgroundThoracoscopic surgery is a primary treatment for lung cancer, with lobectomy and mediastinal lymph node dissection being the predominant surgical approaches for invasive lung cancer. While many thoracic surgeons can proficiently perform lobectomy, thorough and standardized lymph node dissection remains challenging. This study aimed to explore a safer and more efficient surgical method for mediastinal lymph node dissection in lung cancer.MethodsA prospective randomized controlled study was conducted, involving 100 patients with right lung cancer who were admitted to our hospital from January 2021 to April 2024 and met the inclusion criteria. These patients were randomly divided into an observation group (tissue pneumoperitoneum technique around lymph nodes group) and a control group (conventional surgery group). Thoracoscopic lobectomy and mediastinal lymph node dissection were performed. Intraoperative and postoperative related indicators were observed to validate the effectiveness and safety of the tissue pneumoperitoneum technique around lymph nodes.ResultsThe observation group showed a significantly shorter lymph node dissection surgery time compared to the control group, with a statistically significant difference (p < 0.05). The number of lymph nodes dissected in the observation group was significantly higher than that in the control group, with a statistically significant difference (p < 0.05). Although the observation group had slightly more mediastinal lymph node stations dissected than the control group, the difference was not statistically significant (p > 0.05). The total drainage volume within three days postoperatively was comparable between the two groups, with no statistically significant difference (p > 0.05). The observation group had shorter chest tube indwelling time and postoperative hospital stay than the control group, with statistically significant differences (p < 0.05). The incidence of surgical complications was similar between the two groups, and there were no perioperative deaths.ConclusionThe tissue pneumoperitoneum technique around lymph nodes is a more efficient method for mediastinal lymph node dissection in lung cancer, demonstrating safety and feasibility, and is worthy of promotion.